2019
DOI: 10.3389/fmicb.2019.01240
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Bovine Astrovirus-Associated Encephalitis in the Southern Hemisphere (Uruguay), Uncovers Evidence of Viral Introduction to the Americas From Europe

Abstract: Astrovirus species members of the Mamastrovirus genus (family Astroviridae ) have been increasingly recognized as neuroinvasive pathogens in various mammals, including humans, mink, cattle, sheep, and pigs. While cases of astrovirus-associated encephalitis have been reported in North America, Europe, and Asia, their presence has never been documented in the Southern hemisphere. This paper describes a case of astrovirus-associated encephalitis in cattle in Uruguay t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…The estimated mutation rate for RdRp was 2.6×10 −4 /site/year with 95 % highest posterior density (HPD) ranging from 3.3×10 −6 to 6.4×10 −4 /site/year. While the 95 % HPD was large, which is probably due to limited number of sequences analysed, the mean mutation rate was actually close to those derived from human or bovine astroviruses, ranging from 2.8 to 7.4×10 −4 / site /year [24][25][26], demonstrating our mutation rate estimation is authentic. The estimated mutation rate of the CP region was 6.2×10 −4 /site/year (95 % HPD 2.9×10 −5 to 1.3×10 −3 / site/year), which again fell well with the range of previously estimated astrovirus mutation rates.…”
Section: Origin and Past Demography Of Muastv1supporting
confidence: 57%
“…The estimated mutation rate for RdRp was 2.6×10 −4 /site/year with 95 % highest posterior density (HPD) ranging from 3.3×10 −6 to 6.4×10 −4 /site/year. While the 95 % HPD was large, which is probably due to limited number of sequences analysed, the mean mutation rate was actually close to those derived from human or bovine astroviruses, ranging from 2.8 to 7.4×10 −4 / site /year [24][25][26], demonstrating our mutation rate estimation is authentic. The estimated mutation rate of the CP region was 6.2×10 −4 /site/year (95 % HPD 2.9×10 −5 to 1.3×10 −3 / site/year), which again fell well with the range of previously estimated astrovirus mutation rates.…”
Section: Origin and Past Demography Of Muastv1supporting
confidence: 57%
“…The present survey showed a high prevalence of infection with a broad diversity of BoAstV. However, because there is great genetic diversity within the MAstV genus, and this may have implications in pathogenicity [17], further studies are needed to assess whether particular species in this genus are associated with enteric disease in cattle, as seems to be the case for bovine encephalitis linked to MAstV-13 [3,4]. To date, most BoAstVs are not assigned to any of the 19 MAstV species confirmed by the ICTV [9].…”
Section: Discussionmentioning
confidence: 74%
“…Evidence indicates that the BoAstVs that belong to MAstV-13 are associated with neurological diseases and encephalitis [3,4,20], while the other species are not clearly associated to disease, but are excreted in feces [11,13,18,22,23], and/or detected in nasopharyngeal exudates [5]. On the other hand, it is important to study the consequence of asymptomatic cases in the epidemiology and transmission of the virus [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, they have been found worldwide in humans, especially in infants and children, suffering from gastroenteritis, and are among the most common pathogens to cause juvenile diarrhea [1][2][3][4]. In recent years, several studies have identified astrovirus-associated CNS infections in humans, mink, cattle, sheep, pigs, and a muskox [1,2,[5][6][7][8][9][10][11][12][13][14][15][16]. Remarkably, the majority of these neurotropic astroviruses phylogenetically cluster together in the so-called human-mink-ovine (HMO) clade, in which various enterotropic strains are also included [7,8].…”
Section: Introductionmentioning
confidence: 99%